Pengaruh Kemampuan Inisiatif, Kemampuan Berwirausaha, Dan Manajemen Diri Terhadap Kesiapan Kerja Siswa TKR SMK - Haryanto Haryanto; Warju Warju; Soeryanto Soeryanto; Achmad Imam Agung; Puput Wanarti Rusimamto (Educatio, 2026)
This study was conducted to analyze the effects of initiative ability, entrepreneurial ability, and self-management on the work readiness of twelfth-grade TKR vocational high school students in Lamongan Regency. The study employed a quantitative approach with a causal-comparative design. The sample consisted of 152 students, while 34 students were involved in the instrument pilot-testing stage. Data were collected through a Likert-scale questionnaire and subsequently analyzed using multiple linear regression in SPSS 31. The results showed that all three variables had a positive and significant effect on work readiness, both partially and simultaneously, indicating that vocational learning needs to systematically strengthen students’ personal competencies.